Effects of process drama on English speaking competence among undergraduate EFL learners in China - Luo, Shujie; Ismail, Lilliati; Ahmad, Norhakimah Khaiessa binti; Guo, Qian (Sciedu Press, 2025)
Process drama has been widely utilized in educational settings to enhance student engagement and achieve communicative goals. Despite its growing application, there is limited empirical evidence assessing its effectiveness specifically for improving English as a Foreign Language (EFL) speaking competence among undergraduate students in China. This study investigates the efficacy of process drama in enhancing EFL speaking competence among non-English major undergraduates in China. A total of 84 participants were involved, with 42 assigned to an experimental group (EG) that received process drama-based instruction, and 42 to a control group (CG) that followed conventional teaching methods. Data were collected through pre- and post-tests evaluating speaking competence. The analysis employed paired samples t-tests, independent t-tests, and ANCOVA to compare the pre- and post-test results. The results demonstrated significant improvements in speaking competence in both groups; however, ANCOVA revealed that the EG exhibited significantly greater improvement compared to the CG (p = .003). This study confirms that process drama is significantly more effective than conventional teaching methods in enhancing English speaking competence, providing novel insights into the specific benefits of process drama, highlighting its potential to address the limitations of traditional teaching approaches and offering a valuable contribution to the field.